INFLUENCE OF INCUBATION PERIOD ON PHOSPHATE RELEASE IN TWO SOILS OF DISTRICT HYDERABAD - G. M. Kaloi; N. Bhughio; R. N. Panhwar; S. Junejo; A. H. Mari; M. A. Bhutto (Journal of Animal and Plant Sciences, 2011)
Anexperiment was carried out to observe the influence of the incubation period on phosphate release in two soils of District Hyderabad. The samples were treated with the initial phosphorus level of 12.5, 100 and 1000 µg g-1 soil as KH2PO4 dissolved in 0.01 M Ca CL2. The soil solution ratio was 1:10. The samples were incubated for 1-60 days and were shaken for six hours daily on an orbital shaker (150 rpm) at room temperature. It was observed that phosphorus release increased, as the incubation period was less. The native soil phosphorus increased the phosphorus release at same initial phosphorus (PI) levels with increase in incubation period. The phosphate release increased where there was less clay content and more native phosphorus along with increasing initial phosphorus (PI) level. The phosphorus release decreased with more clay content and the increasing incubation period as well as the number of extractions. Thus it was recommended that soils bearing more clay content need higher phosphorus additions before sowing of crop. The soils having less clay content and more native phosphorus requires lower doses of phosphorus because soils have less phosphate adsorbing capacity and adsorbed phosphate could easily be released.
Keywords: Incubation period; phosphorus; clay content; soil